The Soul Purpose - Duckworth, Eleanor (LEARNing Landscapes, 2010)
The author underscores that in any worthwhile educational enterprise there is not one point to be learned—there are infinite points. Using Nicola Sellitto’s insightful "soul purpose" observation as a springboard, she stresses that having no single "point" to convey does not mean doing no teaching. Instead, it means recognizing what enhances the students’ sense of the world’s possibilities, and of their capacity to take part in them. It means keeping the students connected to the possibilities. Drawing on the work of Rauchwerk, Hawkins, Hughes-McDonnell, Cavicchi, Auger and others, she illustrates how teaching students in genuine open-ended settings—in which soul purposes are cultivated—fosters exploratory behaviour, making them eager and engaged learners.